Enhancing catalytic performance of AuPd catalysts towards the direct synthesis of H2O2 through incorporation of base metals. Issue 6 (16th February 2022) - Barnes, Alexandra; Lewis, Richard J.; Morgan, David J.; Davies, Thomas E.; Hutchings, Graham J.
Abstract : The introduction of small quantities of tertiary base metals into supported AuPd nanoparticles is found to result in improved catalytic performance towards the direct synthesis of H2 O2 compared to the bi-metallic analogue. Abstract : The introduction of small quantities of tertiary base metals into supported AuPd nanoparticles results in improved catalytic performance towards the direct synthesis of H2 O2, compared to the bi-metallic analogue. This enhanced activity can be attributed to the electronic modification of Pd and the formation of domains of mixed Pd oxidation state. In particular the introduction of Ni is observed to result in initial rates of H2 O2 synthesis, where the contribution from competitive degradation reactions is negligible, in excess of three times that achieved over the supported AuPd catalyst.